FEAR OF MAKING MISTAKES AS A PSYCHOLOGICAL BARRIER IN ESL CLASSROOMS - Kosimov Bunyod Kosim o’g’li (TADQIQOTLAR, 2025)
Abstract Making mistakes is widely recognized as an essential component of second language acquisition. Nevertheless, many learners of English as a Second Language (ESL) experience a strong fear of making mistakes, which can significantly hinder their communicative development. Despite possessing adequate linguistic knowledge, such learners often remain silent or overly cautious in classroom interactions. This paper argues that fear of making mistakes constitutes a major psychological barrier in ESL learning. It examines the underlying causes of this fear, its effects on language acquisition, and pedagogical strategies that teachers can employ to reduce learners’ anxiety and foster a more supportive learning environment.